Efficacy of ultrasound versus short wave diathermy in the treatment of chronic low back pain in patients with lumbar disk herniation: a prospective randomized control study - Selin Ozen; Sukran Guzel; Huma Boluk Senlikci; Sacide Nur Saracgil Cosar; Ebru Selin Selcuk (BMC, 2023)
Abstract Background Lumbar disk herniation (LDH) is a cause of chronic low back pain (CLBP) treated using physical therapy (PT), including exercise and physical modalities such as ultrasound (US) and short wave diathermy (SWD). Despite the use of US and SWD, there is inconclusive evidence on their efficacy. The aim of this study was to investigate the efficacy of US and SWD in the treatment of CLBP in patients with LDH. Methods A prospective randomized control clinical study. Individuals with radicular CLBP and LDH on magnetic resonance imaging, presenting to the Physical and Rehabilitation Medicine Department were randomized into 3 treatment groups. All participants received 10 sessions of hotpack, transcutaneous nerve stimulation (TENS) and therapeutic exercises. In addition, Group 1 received 10 sessions of therapeutic US (1 MHz, 1.5W/cm2, 10 min), Group 2 SWD (27.12 MHz, wavelength 11.06 m, induction technique, 20 min) to the lower back. Group 3 (control group) received hotpack, TENS and therapeutic exercises alone. Visual analogue scale (VAS) for LBP, Modified Oswestry Disability Index (MODI) and Short Form 36 (SF-36) were evaluated pre and post treatment and at one and three months follow up. Results In all groups, VAS for LBP and MODI improved with treatment and at the one and three month follow up (p < 0.001). In Groups 1 and 2, MODI scores continued to reduce at 1 and 3 months (p < 0.001 and p = 0.012 respectively). SF-36 physical, social function and pain parameters reduced in all groups (p < 0.05). Role limitation due to physical and emotional problems, emotional well-being, vitality and mental health improved in Groups 1 and 2 (p < 0.05). Conclusions Deep heating agents can be used as part of the physical therapy for CLBP in those with LDH with positive mid-term effects. Trial registration NCT03835182, 02/04/2019.